2018
DOI: 10.1159/000489360
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose-Induced Reactive Oxygen Species Stimulates Human Mesenchymal Stem Cell Migration Through Snail and EZH2-Dependent E-Cadherin Repression

Abstract: Background/Aims: Glucose plays an important role in stem cell fate determination and behaviors. However, it is still not known how glucose contributes to the precise molecular mechanisms responsible for stem cell migration. Thus, we investigate the effect of glucose on the regulation of the human umbilical cord blood-derived mesenchymal stem cell (hUCB-MSC) migration, and analyze the mechanism accompanied by this effect. Methods: Western blot analysis, wound healing migration assays, immunoprecipitation, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Furthermore, SNAI1 has been reported to recruit Polycomb Repressive Complex 2 to the E-cadherin promoter to repress E-cadherin expression 23. Recently, Oh et al also reported that high glucose levels enhance the formation of EZH2/Snail complex to facilitate E-cadherin repression and stimulate human mesenchymal stem cell migration 37. All of these studies agree with our finding that increased miR-29a function significantly inhibits the upregulation of SNAI1 in cholestatic liver and primary HSCs.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, SNAI1 has been reported to recruit Polycomb Repressive Complex 2 to the E-cadherin promoter to repress E-cadherin expression 23. Recently, Oh et al also reported that high glucose levels enhance the formation of EZH2/Snail complex to facilitate E-cadherin repression and stimulate human mesenchymal stem cell migration 37. All of these studies agree with our finding that increased miR-29a function significantly inhibits the upregulation of SNAI1 in cholestatic liver and primary HSCs.…”
Section: Discussionsupporting
confidence: 90%
“…3D). This effect is similar to the effect of H 2 O 2 on the migration of DBMSCs [14], MSCs from the chorionic villi [44] and bone marrow [45]. DBMSCs preconditioned with glucose also improved their invasion (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…The ability of transplanted cells to mobilise and migrate to injury sites would enable a direct role in tissue repair and regeneration [ 29 ]. A recent study suggested that high glucose treatment increased human umbilical cord-derived MSC motility and promoted the migration of transplanted MSCs into mouse model wound site [ 30 ]. Human umbilical endothelial cells isolated from GDM pregnancies have also shown an increased migration ability potentially reflecting a proangiogenic GDM state [ 31 ].…”
Section: Discussionmentioning
confidence: 99%